A FORMULATION APPROACH TO QUANTIFY THE ABUNDANCE OF CORAL GENERA - Suharsono, -; Giyanto, - (Marine Research in Indonesia, 2006)
A formulation approach to quantify the abundance of coral genera is considered important to obtain basic information necessary in determining the potency and condition of coral, and one application can also be used to set quota for coral trade. The line intercept method has been used in five different area throughout Indonesian archipelago representing prestine area to heavy disturbances. Based on the number of occurrence, the genera dominance, the size of colony and the coral coverage in each study area was assigned scale, weight and value. The calculation gave the range of Total Value (TV) from 5 -20 and the assignment abundance category of coral genera is 17-20 very common, 14-16 common, 11-13 uncommon, 8 -10 rare, and 5-7 very rare. The categorization of each coral genus of certain area can be used to consider whether it can be harvested or not. Suggestion based on this study as follow: coral genera categorized as "very common" can be harvest, coral genera categorized as "common" can be harvest with caution, coral genera categorized as "uncommon", harvest are limited, coral genera as "rare", harvest are strictly limited and coral genera as "very rare" are prohibited to harvest.